EFFECT OF FOLIAR APPLICATION OF MICRONUTRIENTS AND CANOPY MANAGEMENT ON YIELD AND QUALITY OF GRAPEVINE (Vitis vinfera L) cv. MIRANE - Al-Atrushy, Sh. M. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
A field experiment was carried out at the private vineyard located at Bara-Bhar village, Duhok Governorate, Kurdistan region, Iraq, during the seasons of 2016 and 2017 to investigate the effect of three concentrations of micronutrients (0, 50 and 100 mg.L-1) and determine the optimum bud loads per vine for "Mirane" grapevines. Twelve years old uniform vines were chosen and pruned to four different levels of buds load, namely 36, 44, 48 and 64 buds.vine-1. The factorial experiment within randomized complete block design, with three replication was used. The results showed that the application of micronutrients especially at high concentration significantly increased leaf area, total chlorophyll content, number of clusters. Vine-1, cluster’s weight and yield per vine, as well as weight and size of 100 berries, chemical parameters TSS, total sugar and juice percentage,  juice density and β- carotene in addition to increase mineral content in leaves petiole (Fe, Zn and Mn), whereas the same concentration decreased total acidity and phenols percentage. On the other hand, buds load had significant effect on some characteristics of grapevine. The higher values of leaf area, total chlorophyll, cluster’s weight, weight and size of 100 berries, TSS and total sugars percentage were obtained when the vine was pruned to 36 buds.vine-1. The higher values of number of clusters, yield per vine total phenols and total acidity percentage were obtained when the vine was pruned to 64 bud.vine-1. Highest value of juice percentage was obtained when the vine pruned to 48 buds.vine-1.